An Application of Financial Ratio Analysis on Concordat Firms: A Model Suggestion on Construction Firms Listed in Borsa Istanbul - OZYESIL, Mustafa (Journal of Economics and Behavioral Studies, 2020)
The main purpose of this study is to apply a detailed financial ratio analysis on the firms that have declared concordat, to determine which kind of financial ratios predict the more successful preliminary estimations and to form a model according to the findings obtained and to apply this model to the firms operating in Borsa Istanbul construction sector. For this purpose, the last 5 years’ financial statements of the two companies whose shares are traded on Borsa Istanbul and declared concordat are analyzed by the ratio analysis method. As a result of the analysis, it was found out that the ratios that gave the strongest concordat signal are the liquidity and financial structure ratios. According to the results of the analysis, a model that can be used for the general of the companies is proposed by giving weight to each rate type. In order to test these findings, the model is applied to the financial statements of three companies operating in Borsa Istanbul construction sector and financial ratio scores of firms are calculated over the years. According to the results of the analysis, it is found that the financial situation of the construction firms is much better than the ones of the firms that has declared concordat. However, when the construction firms are compared with each other, it can be stated that YYAPI is lagging behind others in terms of financial performance.